2021
DOI: 10.14485/hbpr.8.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Physical Activity and Screen Time during COVID-19 Pandemic: A Qualitative Exploration of Parent Perceptions

Abstract: Objective: In this study, we explore parent perception of children’s physical activity and screen time during COVID-19 stay-at-home orders. Methods: We interviewed 16 parents of children ages 5-12 years in the St. Louis, Missouri region using snowball sampling. We sampled from rural, urban, and suburban areas. The interviews were recorded, transcribed, and analyzed using a priori and emergent codes. Results: The transition to virtual school and work transformed daily activities. Physical education requirements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 18 publications
2
27
0
1
Order By: Relevance
“…Thirty-four studies (11 cohort, 21 cross-sectional and 2 qualitative) reported changes in physical activity among apparently healthy children and adolescents from before to during the lockdown. Of these, 25 studies (8 cohort and 16 cross-sectional and 1 qualitative)3 27 39–61 observed a decline in physical activity, 8 (2 cohort, 5 cross-sectional and 1 qualitative)9 20 26 62–66 observed no change and 1 (cohort)19 reported an increase in physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-four studies (11 cohort, 21 cross-sectional and 2 qualitative) reported changes in physical activity among apparently healthy children and adolescents from before to during the lockdown. Of these, 25 studies (8 cohort and 16 cross-sectional and 1 qualitative)3 27 39–61 observed a decline in physical activity, 8 (2 cohort, 5 cross-sectional and 1 qualitative)9 20 26 62–66 observed no change and 1 (cohort)19 reported an increase in physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research also reported that the virtual learning model changed daily activities with varied sports education. 4 , 19 Sports education is hampered by an inappropriate understanding of physical activity. 20 , 31 Counseling on the importance of exercise should be modified in accordance with the conditions of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 15–17 Previous research in many countries such as Italy, United States of America, and Saudi Arabia have stated that staying at home causes low physical activity and laziness to become more common, especially among students. 15 , 18 , 19 Sports activities are increasing but not as physical activity; sports are developing in the form of e-sports. 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there are a number of challenges that the Covid-19 pandemic has posed for the role of parents and caregivers of children; indeed, in psychological terms, there has been a need to manage depression and perceived stress in children due to confinement and lack of face-to-face time with peers (Achterberg et al , 2021; Wang et al , 2021), as well as the change in the management and scheduling of routines (Bell et al , 2020), due to the time they have had to spend at home and the difficulties in separating their school and family interaction contexts. Additionally, relationships with peers and family members have undergone forced changes (Soltero-González and Gillanders, 2021), making the notion of entertainment and use of free time a complex issue to address (Donati et al , 2021; Eyler et al , 2021), which also leads to drastic changes in media use and access (Kotrla Topić et al , 2021; Werling et al , 2021). Future research may aim to investigate how this post-pandemic context has affected the level of parents’ mobile AL and its possible relationship with different parenting styles.…”
Section: Discussionmentioning
confidence: 99%